NEW HOST RECORD FOR GENDRIA SPECIES FROM THE INTESTINE OF MARINE FISH PLATYCEPHALUS SČABER (LINNAEUS) FROM KAKINADA, ANDHRA PRADESH - LAKSHMI, B. BHARATHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
A female specimen of Gendria sp. has been obtained from the intestine of Platycephalus scaber (L.). P. scaber represents a new host and new locality record. A detailed description of the specimen has been furnished. In the course of survey of parasites of marine fishes from Kakinada, a careful examination of intestine of Platycephalus scaber (L.), a common fish of this coast, yielded an interesting female nematode individual. It has been proved to be a member of the genus Gendria.